1998
DOI: 10.1007/bf03012457
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of clonidine as an analgesic in paediatric adenotonsillectomy

Abstract: Purpose: To compare the analgesic effects of preoperative oral clonidine with intraoperative intravenous fentanyl in children undergoing tonsillectomy or adenotonsillectomy. Methods: This randomized, controlled, double-blind study of 36 ASA I-II children, age 7-12 yr undergoing adenotonsillectomy was conducted at a tertiary care paediatric teaching hospital. Either 4 lug'kg q clonidine p0 was given 60-90 rain preoperatively or 3/~g-kg -s fentanyl iv was given intraoperatively. Postoperatively visual analog pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 11 publications
2
32
0
4
Order By: Relevance
“…Clonidine 3µg/kg used by Ramesh et al showed sedation effect comparable to diazepam (10) . Clonidine 4µg/kg used by Mikawa et al, Remier et al, Batra et al and Malde et al (3,5,8,10,13,14) . They found that clonidine 4µg/kg had better sedation, anxiolysis and attenuation of haemodynamic response than diazepam.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…Clonidine 3µg/kg used by Ramesh et al showed sedation effect comparable to diazepam (10) . Clonidine 4µg/kg used by Mikawa et al, Remier et al, Batra et al and Malde et al (3,5,8,10,13,14) . They found that clonidine 4µg/kg had better sedation, anxiolysis and attenuation of haemodynamic response than diazepam.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…A ineficácia apresentada pela clonidina, por via enteral, neste estudo, em potencializar os efeitos sedativos em crianças submetidas à VM, poderia ser atribuída a: a) Não efetividade do fármaco: vários estudos já demonstraram a eficácia da clonidina, tanto como sedativos 2,4,7, 18,20,[21][22][23][24][25][26][27][28] , como no tratamento da abstinência 2-4,5,9, 12,16,17,19,29 . Em alguns estudos, quando utilizada para sedação leve, a clonidina teve resultados comparáveis ao fentanil, evitando doses extras de sedativos 21 . Em apenas um estudo a clonidina e o placebo não apresentaram diferenças 6 .…”
Section: Discussionunclassified
“…Clonidine is an effective analgesic in this situation, 11,19 although over-sedation would be a concern in patients with OSAS. Preoperative acetaminophen seems to be a useful intervention for minor procedures such as myringotomy.…”
Section: Analgesicsmentioning
confidence: 99%